Double Dissociations in the Processing of Conceptual Relations - Vivas, Leticia Yanina (2014)
The aim of the present paper is to analyze if taxonomic and thematic conceptual relations are processed primarily in the linguistic system, in the simulation system or in both. Because the verbal modality is the best way to access the linguistic system and the pictorial modality is the best way to access the simulation system (Barsalou, 1999), we studied these processes through verbal and pictorial tasks. We studied a group of 60 patients with focal brain lesions to explore the presence of double dissociation, based on the assumption that such patients will reveal the existence of independent processes according to conceptual relation type and the modality in which information is presented (verbal vs. pictorial). The results reveal the presence of double dissociations in the processing of thematic relations, but not in taxonomic relations. This suggests that there may be two ways to store relations of this type: through the co-occurrence of words in language or through the joint representation of both objects in a contextual representation. The thematic relations may be primordially stored within one of the two systems (linguistic and simulation) or both. Taxonomic relations, on the other hand, are principally processed in the simulation system.